Silk–ionomer and silk–tropoelastin hydrogels as charged three‐dimensional culture platforms for the regulation of hMSC response. (6th April 2016) - Calabrese, Rossella; Raia, Nicole; Huang, Wenwen; Ghezzi, Chiara E.; Simon, Marc; Staii, Cristian; Weiss, Anthony S.; Kaplan, David L.
Abstract: The response of human bone marrow‐derived mesenchymal stem cells (hMSCs) encapsulated in three‐dimensional (3D) charged protein hydrogels was studied. Combining silk fibroin (S) with recombinant human tropoelastin (E) or silk ionomers (I) provided protein composite alloys with tunable physicochemical and biological features for regulating the bioactivity of encapsulated hMSCs. The effects of the biomaterial charges on hMSC viability, proliferation and chondrogenic or osteogenic differentiation were assessed. The silk–tropoelastin or silk–ionomers hydrogels supported hMSC viability, proliferation and differentiation. Gene expression of markers for chondrogenesis and osteogenesis, as well as biochemical and histological analysis, showed that hydrogels with different S/E and S/I ratios had different effects on cell fate. The negatively charged hydrogels upregulated hMSC chondrogenesis or osteogenesis, with or without specific differentiation media, and hydrogels with higher tropoelastin content inhibited the differentiation potential even in the presence of the differentiation media. The results provide insight on charge‐tunable features of protein‐based biomaterials to control hMSC differentiation in 3D hydrogels, as well as providing a new set of hydrogels for the compatible encapsulation and utility for cell functions. Copyright © 2016 John Wiley & Sons, Ltd.